Teachers’ Conceptualisations and Needs in Developing Foreign Language Literacy Skills at Primary Level (Croatian Journal of Education - Hrvatski časopis za odgoj i obrazovanje, 2021)
As many European countries have introduced English language teaching at preprimary and primary levels, the need for effective development of foreign language literacy skills has proved to be essential. Traditionally, literacy is defined as the ability to read and write. However, broader definitions include understanding of a wide range of texts and the ability to communicate in multilingual environments. Most teacher education programmes do not provide sufficient training for the development of initial and basic foreign language literacy skills of learners, and teachers feel they do not receive enough support in this area. As a result, Slovenian pupils of English are the least proficient in reading of all the language skills, with 12 % of them failing to reach A1 level in reading and 29 % remaining at this level at the end of primary school (European Commission, 2012). The aim of the present study was to investigate the perceptions of English teachers (N=112) regarding the development of foreign language literacy skills in Slovenian primary schools. For this purpose, a questionnaire was used to research how teachers conceptualise the development of FL literacy, how they assess pupils’ difficulties with reading and writing tasks and the literacy areas in which they think they would need more support in their teaching. A quantitative approach and a content analysis of the open questions were used. The differences between the teacher groups were measured with the Chi-square test. The study indicated teachers’ restricted views on the meaning of literacy in the open questions, while the closed questions implied a broader understanding of the concept. Most teachers expressed a desire to gain more professional knowledge in this area. The results of the study will provide a starting point for developing more effective teacher training programmes in foreign language literacy and for supporting in-service teachers in developing foreign language literacy at primary level. Budući da su mnoge europske države uključile poučavanje engleskoga jezika na predškolskoj i osnovnoškolskoj razini, potreba za učinkovitim razvojem jezičnih vještina na stranom jeziku pokazala se važnom. Tradicionalne definicije određuju pismenost kao sposobnost čitanja i pisanja, a šire definicije pismenosti uključuju razumijevanje širokoga raspona tekstova i sposobnost komunikacije u višejezičnom okruženju. Većina programa obrazovanja učitelja ne osposobljava ih dovoljno za razvoj inicijalnih i osnovnih vještina pismenosti učenika na stranom jeziku, a sami učitelji smatraju da ne dobivaju dovoljno podrške u ovom području. Zahvaljujući tome najmanje razvijena jezična vještina slovenskih učenika engleskoga jezika je čitanje: 12 % učenika ne uspijeva dosegnuti A1 razinu čitanja, a 29 % učenika ostaje na ovoj razini na kraju osnovne škole (Europska komisija, 2012). Cilj ovoga istraživanja bio je ispitati percepcije razvoja vještina pismenosti na engleskom jeziku učitelja engleskog (N = 112) u slovenskim osnovnim školama. Pri tome je korišten upitnik kojim se nastojalo utvrditi konceptualizacije razvoja pismenosti na stranom jeziku učitelja, njihove procjene učeničkih teškoća u čitanju i pisanju te područja pismenosti u kojima smatraju da im treba više podrške u poučavanju. U istraživanju je upotrijebljen kvantitativni pristup i analiza sadržaja za odgovore na pitanja otvorenoga tipa. Razlike između skupina učitelja izmjerene su Hi-kvadrat testom. Rezultati istraživanja ukazuju na učiteljsko ograničeno viđenje značenja pismenosti u pitanjima otvorenoga tipa, dok pitanja zatvorenoga tipa ukazuju na šire razumijevanje koncepta. Većina učitelja izrazila je želju za stjecanjem dodatnoga profesionalnog znanja u ovom području. Rezultati istraživanja predstavljaju polaznu točku za razvoj učinkovitijih programa obrazovanja učitelja u području pismenosti na stranom jeziku i podršku zaposlenim učiteljima u razvoju pismenosti na stranom jeziku na razini osnovne škole.